The Swedish COVID-19 approach: a scientific dialogue on mitigation policies - Björkman, Anders; Gisslén, Magnus; Gullberg, Martin; Ludvigsson, Johnny (Frontiers in Public Health, 2023)
During the COVID-19 pandemic, Sweden was among few countries which did not adopt strict lockdown but relied more on migaon recommendaons on a voluntary sustainable basis. While supported by the majority of Swedes, this approach, was rapidly and connuously cricized. Respecul debate about scienfic evidence was oen replaced by mudslinging. Available data on excess all-cause mortality rates, however, indicate that Sweden experienced relavely fewer deaths per populaon unit during the pandemic (2020-2022) than most other high-income countries and comparable to neighboring Nordic countries. An open objecve scienfic dialogue is essenal for learning and being beter prepared for future outbreaks.